2018
DOI: 10.1177/1526602818821193
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Treatment of Limb Occlusion of the Anaconda Endograft After Endovascular Aneurysm Repair

Abstract: To evaluate the incidence and treatment of limb occlusions of the second-and third-generation Anaconda endografts. Methods: A single-center retrospective study was conducted involving 317 consecutive patients (mean age 76 years; 289 men) who underwent endovascular aneurysm repair for elective asymptomatic, symptomatic intact, and ruptured infrarenal abdominal aortic aneurysm with 2 versions of the Anaconda device. From September 2003 to July 2011, the second-generation device was used in 189 patients (mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…24 Recently, Rödel et al focused on this specifically and reported a 9.8% rate of index occlusions over a mean follow up of 47 months. 32 They showed no significant difference in overall occlusion rate between the second and third generation Anaconda devices, or with use within the IFU or not. No endograft escapes this complication, 33 and Faure et al looked for predictive factors for limb occlusion in various types of endografts.…”
Section: Discussionmentioning
confidence: 91%
“…24 Recently, Rödel et al focused on this specifically and reported a 9.8% rate of index occlusions over a mean follow up of 47 months. 32 They showed no significant difference in overall occlusion rate between the second and third generation Anaconda devices, or with use within the IFU or not. No endograft escapes this complication, 33 and Faure et al looked for predictive factors for limb occlusion in various types of endografts.…”
Section: Discussionmentioning
confidence: 91%
“…Extreme iliac artery angulation >60%, circumferential calcification or thrombus >50%, extreme iliac limb graft oversizing, and extension to the external iliac artery are factors contributing to iliac limb thrombosis. 18 Rodel et al 19 evaluated the incidence and treatment of limb graft occlusions of the second- and third-generation Anaconda stent-grafts. No significant difference in overall occlusion rate between the second-generation devices or with regard to IFU compliance was reported; however, there was a decrease in the occlusion rate for elective patients treated with the third-generation device.…”
Section: Discussionmentioning
confidence: 99%
“…43 Possibly related to this, the second-generation infrarenal Anaconda™ endograft was prone to limb occlusion, thought to be related to compression of the limbs due to a mismatch between the J o u r n a l P r e -p r o o f smaller main body and relatively large limb diameters. 17,44 To allow for easier limb size selection, the third-generation graft (ONE-LOCK™) was launched in 2011, with a standardized proximal docking zone and different types of distal limb configurations (straight, flared or tapered). 17 Most of the reported experience with the Anaconda™ endograft comes from secondgeneration devices.…”
Section: Discussionmentioning
confidence: 99%
“…17,44 To allow for easier limb size selection, the third-generation graft (ONE-LOCK™) was launched in 2011, with a standardized proximal docking zone and different types of distal limb configurations (straight, flared or tapered). 17 Most of the reported experience with the Anaconda™ endograft comes from secondgeneration devices. 15,16,24,25 Only one reported study has included only third-generation devices 23 and a few studies included mixed populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation